Review of the predaceous diving beetles of the genus Hydaticus Leach, 1817 (Coleoptera: Dytiscidae) of Kazakhstan - Temreshev, I. I. (Acta Biologica Sibirica, 2018)
The genus Hydaticus Leach, 1817 (Coleoptera: Dytiscidae) in Kazakhstan is reviewed including diagnoses, illustrations, distributions, and natural history. An annotated checklist of the 7 species of the genus occurring in Kazakhstan is presented. They belong to the subgenus Hydaticus (s. str.) with 4 species: H. aruspex Clark, 1864, H. continentalis J. Balfour-Browne, 1944, H. seminiger DeGeer, 1774, H. transversalis Pontoppidan, 1763, and to the subgenus Prodaticus Sharp, 1882 with 3 species: H. grammicus Germar, 1827, H. pictus Sharp, 1882, H. ponticus Sharp, 1882. H. aruspex and H. seminiger are recorded in Kazakhstan for the first time.